Redescription of Arcotheres tivelae (Gordon, 1936), a pea crab endemic to the Persian Gulf and Gulf of Oman (Crustacea: Decapoda: Brachyura: Pinnotheridae) - Ng, Peter K. L.; Clark, Paul F.; Naderloo, Reza (Zootaxa, 2022)
The taxonomy of the pinnotherid crab, Pinnotheres tivelae (Gordon, 1936), now assigned to Arcotheres Manning, 1993, is revised. Type specimens from Muscat, Gulf of Oman, are compared with extensive material from the type locality and Persian Gulf. Arcotheres tivelae is shown to be a valid species, is redescribed, figured to modern standards and males are reported for the first time. This species had been confused with A. placunae (Hornell & Southwell, 1909) from Pakistan and western India, but the two species can be distinguished by the morphology of the carapace, third maxilliped, ambulatory leg features and characters of the male first gonopod. Arcotheres tivelae is morphologically closest to three other species also found in venerid clams, A. exiguus (Bürger, 1895), A. rayi Ahyong & Ng, 2007, and A. obesus (Dana, 1852), but the distal morphology of its male first gonopod is distinct from its congeners. Furthermore, A. tivelae is recorded from Kuwait for the first time.